Agreement of skin test with IL-4 production and CD40L expression by T cells upon immunotherapy of subjects with systemic reactions to Hymenoptera stings. (February 2016) - Urra, José M.; Cabrera, Carmen M.; Alfaya, Teresa; Feo-Brito, Francisco
Highlights: Hymenoptera venom immunotherapy reduces the expression of CD40L and CTLA-4 on T CD4 lymphocytes. Hymenoptera venom immunotherapy decline the IL-4 producing T lymphocytes and increase IFN-γ producing T lymphocytes. The modifications induced by immunotherapy on IL-4 and CD40L link to those seen in skin test. Neither basophil activation test nor the sIgE levels, are not linked to the immune changes induced by immunotherapy. Abstract: Venom immunotherapy is the only curative intervention for subjects with Hymenoptera venom allergy who suffering systemic reactions upon bee or wasp stings. Venom immunotherapy can restore normal immunity against venom allergens, as well as providing to allergic subjects a lifetime tolerance against venoms. Nevertheless, it is necessary using safety assays to monitoring the development of tolerance in the VIT protocols to avoid fatal anaphylactic reactions. The purpose of this study was to assess the modifications in several markers of tolerance induction in subjects with Hymenoptera venom allergy undergoing immunotherapy. The studies were performed at baseline time and after six month of VIT. Intradermal skin tests, basophil activation tests, specific IgE levels; and the T-cell markers (IL-4 and IFN-γ producing cells; and expression of the surface activation markers CD40L and CTLA-4) were assayed. At six month of imunotherapy all parameters studied had significant alterations. All decreased, except the IFN-γ producing cells. In addition, modifications in intradermal skin test showed a significant correlation with both, CD40L expression on CD4 T lymphocytes ( p  = 0.043) and IL-4 producing T lymphocytes ( p  = 0.012). Neither basophil activation test nor serum levels of sIgE demonstrated any correlation with the immunological parameters studied nor among them. These results suggest that both IL-4 production and CD40L expression could be two good indicators of the beneficial effects of venom immunotherapy which translate into skin tests.